Impact of early Danian environmental perturbations on mid-latitude planktic foraminiferal assemblages from the ODP Site 1262 (South Atlantic Ocean) - Krahl, Guilherme; Arenillas, Ignacio; Gilabert, Vicente; Kochhann, Karlos G. D.; Bom, Marlone H. H.; Fauth, Gerson; Arz, José Antonio (Zenodo, 2023)
After the mass extinction at the Cretaceous/Paleogene (K/Pg) boundary (~66 Ma), life forms quickly radiated to occupy ecological niches in the world’s oceans. Nevertheless, the aftermath of the Chicxulub impact, the massive volcanism of the Deccan Traps and climatic perturbations endured during the early Danian. The impact of consequent carbon cycle perturbations on nascent plankton communities, such as the Dan-C2 event (~65.80 to ~65.71 Ma), is still poorly known. In this work, we present a detailed study of planktic foraminiferal assemblages from Ocean Drilling Program (ODP) Site 1262 (Walvis Ridge, South Atlantic Ocean), spanning the first ~400 kyr of the Danian. No relevant perturbations in planktic foraminiferal assemblages and carbonate preservation indices have been identified at Site 1262 during the Dan-C2 event. Approximately 50 kyr before the beginning of the Dan-C2 event, a Hg-rich interval, potentially linked to the emplacement of the Ambenali Formation of the Deccan Traps massive volcanism, is recorded between ~65.95 and 65.82 Ma. It coincides with an increase in aberrant planktic foraminifera (~65.93 to ~65.82 Ma), allowing to establish a cause-effect relationship. Additionally, a bloom of triserial guembelitriids was recognized between ~65.87 and ~65.78 Ma, also preceding the Dan-C2 event but lagging the Hg-rich interval and the bloom of aberrant planktic foraminifera. The lag time between the first volcanic episode and ecosystem response may be due to factors such as an inefficient biological pump and increases in temperature, microbial activity and food supply at the ocean surface. A second Hg-rich interval identified between ~65.70 and ~65.65 Ma has been tentatively tied to the Mahabaleswar Formation of the Deccan Traps. Neither the second volcanic episode nor the Dan-C2 event resulted in relevant environmental perturbations at Site 1262. This suggests that, although volcanism may have had an impact on early plankton communities in the early Danian through metal contamination, marine ecosystems ...